2021
DOI: 10.1002/mde.3379
|View full text |Cite|
|
Sign up to set email alerts
|

Impact mechanism of supervisor developmental feedback on employee workplace learning

Abstract: Based on the mental simulation duality, this paper adopts the expected successful performance and self‐goal setting as mediating variables and takes the dual system theory. This paper constructs a chain mediating model in which supervisor developmental feedback affects employee workplace learning. A study of 449 samples proves that supervisor developmental feedback can significantly improve employee workplace learning; expected successful performance and self‐goal setting are significant independent mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Current research on supervisors’ influence on employees’ behavior has focused mainly on supervisors’ traits [ 58 ], and the theoretical basis of research on SDF is more limited. Although previous studies have related SDF to employees’ cognition and behavior from an interactionist point of view [ 19 ], social exchange theory [ 17 ], and social cognitive theory [ 18 ], the linkage from SDF to JS, as well as the mediating effect of ER, have not been established. COR theory expands the scope of interpretation for the effect of SDF, which regards SDF as a resource for employees, thus providing a new perspective to explain the relationship between SDF and employee JS and enriching and expanding the findings on the influence of SDF on employees’ psychology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current research on supervisors’ influence on employees’ behavior has focused mainly on supervisors’ traits [ 58 ], and the theoretical basis of research on SDF is more limited. Although previous studies have related SDF to employees’ cognition and behavior from an interactionist point of view [ 19 ], social exchange theory [ 17 ], and social cognitive theory [ 18 ], the linkage from SDF to JS, as well as the mediating effect of ER, have not been established. COR theory expands the scope of interpretation for the effect of SDF, which regards SDF as a resource for employees, thus providing a new perspective to explain the relationship between SDF and employee JS and enriching and expanding the findings on the influence of SDF on employees’ psychology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, employees would rather connect with and receive recognition from those in higher-ranking positions inside the organization than with and from their colleagues [ 15 , 16 ]. However, recent studies in organizational behavior have confirmed the reality of SDF and investigated its beneficial effects on employees’ behaviors [ 17 , 18 ]. A more in-depth and methodical investigation into how and when SDF influences employees’ JS needs to be conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-goal setting. Referring to previous studies (Zeijen et al ., 2018; Wang and Zhang, 2021), we used the self-goal setting subscale taken from the self-leadership scale developed by Houghton and Neck (2002). This scale had a total of 5 items (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In the article (Wang & Zhang, 2022), the published article contains errors in Figure 1. The correct Figure 1 is shown below.…”
mentioning
confidence: 99%